Student Writing Intensive: Group B / Resource Pack - Institute for Excellence in Writing; Pudewa, Andrew (Institute for Excellence in Writing c 2013.)
Educate and entertain your junior high students with Andrew Pudewa's engaging language arts seminar! Based on the principles of his award-winning Teaching Writing: Structure and Style course, 15 lessons cover outlines; paragraph writing; story sequencing; summarizing and working from multiple references; creative writing; banned words; dress-ups; and more.
Grade 4
Age 8-11
Keywords: Writing -- Manuals, Handbooks etc; Writing Curriculum